Answer:
+3.464; -3.464
Explanation:
call A = y + 2x + 1 = 0 => y = (1 - 2x)
call B: 4y - 4(x^2) - 12x = -7
=> replace y from A to B =>
- 4(1 - 2x) - 4(x^2) - 12x = -7
- 4 - 8x - 4(x ^ 2) - 12x = -7
- -8x - 4(x ^ 2) - 12x = -7 - 4 = -11
- -4(x^2) - (8x - 12x) = -11
- -4(x^2) + 4x = -11
- -4(x^2) + 4x + 11 = 0
=> get delta Δ = (-4^2) - 4*(-4 * 11) = 192
=> Δ > 0 => got 2 No
=> x1 =
=
= -1.232
=> x2 =
=
= 2.232
=> replace x from B into A
=> y1 = (1 - 2x) = (1 - 2 * -1.232) = 3.464
=> y2 = (1 - 2x) = (1 - 2 * 2.232) = - 3.464